Advancements in SELEX Technology for Aptamers and Emerging Applications in Therapeutics and Drug Delivery - Liangjie Feng; Yu Sun; Wenshen Jia; Yang Yu; Chang Liu; Jing Yang; Yunxia Luan; Jin Chen; Fengchao Wang (Biomolecules)
Nucleic acid aptamers, selected through the Systematic Evolution of Ligands by Exponential Enrichment (SELEX), are short nucleic acid sequences that exhibit high affinity and specificity towards diverse targets. Over the past three decades, substantial advancements have been made in both the technology and applications of nucleic acid aptamers. This review provides an in-depth analysis of the historical development and defining characteristics of aptamers, highlighting recent technological innovations in SELEX, including Capillary Electrophoresis SELEX, Microfluidic SELEX, Cell-SELEX, and others. We explore the applications of aptamers in therapeutic and targeted drug delivery, emphasizing their advantages over traditional antibodies such as cost-effectiveness, ease of synthesis, and lower immunogenicity. Key challenges such as stability, specificity, and efficient delivery are discussed, with proposed strategies for improvement including advanced chemical modifications and integration with nanotechnology. By integrating advanced technologies, aptamers hold significant promise for enhancing precision medicine and personalized therapeutic interventions, offering new avenues for the treatment of complex diseases.